The powerless bosses: the working day experience of bicycle messengers and its impact on their identities and wellbeing - Iben Østin Hjelle; Helle Nordrum; Julian-Werner Wentzeck; Ali Teymoori (BMC Psychology)
Abstract Background Bicycle messengers in the online food delivery sector typically work on an on-demand basis, have digitally mediated relationships with their employer, and have very limited labor rights. In this study, we explore how bicycle messengers themselves experience their workday and how platform work influences their identity and wellbeing. Method We conducted qualitative interviews with ten bicycle messengers working for Foodora and Wolt in Bergen and Oslo, Norway. We used reflexive thematic analysis to analyze the interviews. Results We discerned five themes related to the dynamics of autonomy versus algorithmic control, the reduction of workers’ identity to the courier role, lack of collegial bonding among bicycle messengers, physical demands and risks of the job, and the transitory nature of courier work. Conclusion The working experience of bicycle messengers is marked by a paradoxical sense of autonomy and powerlessness in the face of algorithmic control, a perceived sense of devaluation by others and its reproduction among their own colleagues, and competitive and at times hostile intra- and inter-group dynamics. We explore the implications of such working experiences for bicycle messengers’ wellbeing and identity within this newly evolving form of labor.